Pengaruh Gaya Kepemimpinan Manajer dan Komitmen Organisasi terhadap Kinerja Pegawai Melalui Budaya Organisasi di PT. Berca Mandiri Perkasa - Teguh Mulyono (Politeknik Kelapa Sawit Citra Widya Edukasi, 2016)
The purpose of this study was to assess the influence of style leadership managers and commitment organization, culture organization of the performance of employees. Data collected by using instrument that measures the variables. Calibration instrument done to test the validity of its grains and coefficients reliability, validity grains calculated by using product moment coefficient, and reliability calculated by applying the alpha croncbach coefficient. The model used in this research was model causality or relation influence. To test hypotheses that will be brought in research and technique analyst who will be used is the path analysis. The results of the study concluded the influence of total style leadership of the performance of employees of 0.8262 .This showed that style leadership already impact to performance employees. With value of 0.8262 showed strongly impact to style of leadership through culture organization; while the influence of total commitment to organization of employee performance of 0.34. It showed commitment organization have an strong against performance, through culture organization that had been formed.